2009
DOI: 10.1002/jbm.a.32582
|View full text |Cite
|
Sign up to set email alerts
|

Development and biocompatibility of a novel corrodible fluoride‐coated magnesium‐calcium alloy with improved degradation kinetics and adequate mechanical properties for cardiovascular applications

Abstract: Recently, corrodible magnesium-based alloys have been introduced for use as cardiovascular stents and orthopedic implants. However, rapid corrosion rates have raised questions about their biocompatibility. Therefore, we developed a binary fluoride-coated magnesium-calcium alloy with improved degradation kinetics. Biocompatibility of the alloys was evaluated with metabolic assays (colorimetric WST-1 test). Furthermore, five different probes of magnesium-calcium alloys (MgCa 0.4, 0.6, 0.8, 1.2, and 2.0 wt %) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
94
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 119 publications
(100 citation statements)
references
References 30 publications
5
94
0
1
Order By: Relevance
“…As described in previously published articles 20,22 we started our investigations in living systems with the assessment of single elements (iron and manganese in form of appropriate salts) of the new developed FeMn alloys-no increase in metabolic activity was observed for both metals, but a significant dose-dependent decrease. The tested Feund Mn-metal salts led to a decrease in metabolic activity, dose-and time-dependently.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As described in previously published articles 20,22 we started our investigations in living systems with the assessment of single elements (iron and manganese in form of appropriate salts) of the new developed FeMn alloys-no increase in metabolic activity was observed for both metals, but a significant dose-dependent decrease. The tested Feund Mn-metal salts led to a decrease in metabolic activity, dose-and time-dependently.…”
Section: Discussionmentioning
confidence: 99%
“…19 Fluoride coating has been shown to delay the degradation process; however, corrosion still occurs at undesirably rapid rates. 20,21 Although pure iron has been shown to exhibit excellent biocompatibility, 22 the corrosion rates are too slow to be suitable for pediatric cardiovascular devices.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al provide a compact overview of the basic methods available for surface treatment [35]. They hint to microarc oxidation [116], anodising [117], evaporation [118], alkaline heat treatment [119], fluoride coating [120], electro deposition [121], phosphate coating [122], shock peening [123], ion implantation [124], physical vapour enrichment [125] and polymer coating [126]. The aim of the process is always to reduce the oxidation tendency of the surface of the magnesium alloy or to provide the surface with a protective layer.…”
Section: Increasing the Corrosion Resistancementioning
confidence: 99%
“…Gu et al (Gu, Zheng et al 2009) reported good biocompatibility of magnesium with various alloying elements, recommending Al and Y for stents and Al, Ca, Zn, Sn, Si and Mn for orthopaedic implants. Drynda et al (Drynda, Hassel et al 2010) developed and evaluated fluoride coated Mg-Ca alloys for cardiovascular stents, reporting good biocompatibility and better degradation behaviour. However, as pure magnesium has been found to corrode too quickly in the low pH environment of physiological systems, much effort has also been placed into developing alloys or coatings to limit its degradation behaviour (Zeng, Dietzel et al 2008).…”
Section: New Vocal Fold Wound Closure Device -Bioabsorbable Microclipsmentioning
confidence: 99%